Corporate Charity for 'the House': Craft Pensions and the Widows' Fund, 1670–1782. Issue 2 (August 2022) - Allen, Aaron
Abstract : This article focuses on charitable provision for craft widows and the development of new ways of meeting the challenges of caring for them. The craft guild was an important part of Europe's urban social structures. It is popularly understood as having offered a safety net for members and their families through old age and the experience of bereavement. Taking for example the Edinburgh building trades, which incorporated ten distinct arts under the title of 'Incorporation of Mary's Chapel', important aspects of corporate charitable provision are brought to light. The incorporation referred to themselves as 'the House', laying claim to their place as one of the building blocks of a godly society, but were they always able to provide for their households? Previously underused sources give fresh insights into the difficulties faced by the House in meeting the needs of their widows. From the eighteenth century, innovative forms of provision were instituted, which were an entitlement rather than discretionary, but for most of the incorporation's history, charity depended on the state of their finances. This meant difficult decisions for those in charge, which raises questions about the assumption that membership of a craft guild guaranteed an economic safety net.